An exploration of student midwives perceptions and experiences of working with women who have post natal illness - Alex, Shaw (2014)
Abstract Midwives are expected to manage caseloads of women with a range of physical and psychological issues. This study aims to explore student midwives’ views of working with mental health problems and offers an insight into the education they receive in order to practice as competent midwives. The study undertook semi-structured interviews with seven undergraduate student midwives all in their final year of study. Analysis of the transcribed interviews resulted in four key themes emerging: apprehension, education, mental health problems and support, and midwifery. The findings of this research are used to suggest implications for both midwifery and nursing practice.